Analisis Pola Komunikasi Kemenkes Melalui Instagram @kemenkes_ri dalam Meningkatkan Awareness Penggunaan Antibiotik - Riani, Nurul Izzah; Ihsan, Muhammad Fadhiel (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Antibiotic resistance is a major topic of discussion and the number of cases often increases every time, so that the Ministry of Health of the Republic of Indonesia (Kemenkes RI) continuously produces various kinds of information related to the dangers of non-compliance with the use of antibiotics through its social media. The aim of this research was to determine how much attention the public pays to content uploaded by the Ministry of Health related to awareness of compliance with antibiotic use. The research method was carried out qualitatively with triangulation data collection techniques. The results of research conducted by analysis of 4 uploaded content from the @kemenkes_ri Instagram account showed that poster type content on January 5 2025 received the highest engagement rate, namely 0.408%, followed by an upload on November 25 2024 which contained two short video uploads. 0.05% and live broadcast videos 0.08%, but content uploaded on December 11 2024 has the lowest engagement rate, namely 0.009% with live video content type. So, it can be concluded that currently the public is paying attention to this situation as can be seen in the comments column and also the number of shares shows a large number when compared to the content in previous uploads.